2019
DOI: 10.1371/journal.pone.0214665
|View full text |Cite
|
Sign up to set email alerts
|

Projected heat stress challenges and abatement opportunities for U.S. milk production

Abstract: Cost-effective heat mitigation strategies are imperative for maintaining milk production and dairy farm profitability in the U.S. with projected climate change. This study investigated the cost-effectiveness of four heat abatement strategies, including Minimal (open barn or shading), Moderate (forced ventilation), High (fans and misting), and Intense (air conditioning). Heat stress and subsequent impacts on milk production per cow were predicted across nine climatic regions in the U.S. for early (2015 to 2034)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 54 publications
0
23
0
Order By: Relevance
“…Because genetically altering the thermal tolerance of high producing animals is difficult (120), and there are many reviews that cover nutritional and metabolic responses and nutritional management for heat-stressed dairy cattle [i.e., (119,121)], this section will briefly review heat abatement by physical modification of the environment. A recent analysis predicts that the milk production loss due to heat stress increases at a rate of 174 ± 7 kg/cow/decade in the 21st century, but implementation of intensive cooling using fans, water or air conditioning minimizes the loss of milk yield and is associated with significant economic return for dairy producers (122). Therefore, heat abatement is an efficient and profitable approach to alleviate the negative impacts of heat stress and is the essential component of heat stress management on dairy farms.…”
Section: Management Interventionsmentioning
confidence: 99%
“…Because genetically altering the thermal tolerance of high producing animals is difficult (120), and there are many reviews that cover nutritional and metabolic responses and nutritional management for heat-stressed dairy cattle [i.e., (119,121)], this section will briefly review heat abatement by physical modification of the environment. A recent analysis predicts that the milk production loss due to heat stress increases at a rate of 174 ± 7 kg/cow/decade in the 21st century, but implementation of intensive cooling using fans, water or air conditioning minimizes the loss of milk yield and is associated with significant economic return for dairy producers (122). Therefore, heat abatement is an efficient and profitable approach to alleviate the negative impacts of heat stress and is the essential component of heat stress management on dairy farms.…”
Section: Management Interventionsmentioning
confidence: 99%
“…However, in extreme heat, providing shade alone is insufficient, since it has no impact on environmental temperature or relative humidity. In these circumstances, active cooling is required (St-Pierre et al, 2003;Tucker et al, 2008;Gunn et al, 2019). St-Pierre et al (2003) identified three different models of cooling system using fans and/or forced ventilation, combination of fans and sprinklers, and high-pressure evaporative cooling to abate moderate, high and intense heat respectively in the dairy farm.…”
Section: Mitigation Of Heat Stressmentioning
confidence: 99%
“…Later, different equations were developed for different livestock species that could be used in heat stress impact studies. During the past decade, several studies tried to use different THI indices to assess heat stress conditions on dairy cattle under future conditions across global and regional scales (e.g., Hernández et al 2011;McCabe et al 2016;Gunn et al 2019). For example, Lallo et al (2018) investigated heat stress conditions for different livestock in the Caribbean and concluded that ruminants will experience higher heat stress under a future climate as compared with present-day conditions, and that this will threaten their productivity.…”
Section: Introductionmentioning
confidence: 99%